Carboxymethylcellulose hydrogels cross-linked with magnetite nanoparticles for the removal of organic and inorganic pollutants from water. Issue 4 (August 2017) - Uva, M.; Tambasco, M.; Grassi, G.; Corsi, I.; Protano, G.; Atrei, A.
Graphical abstract: Highlights: CMC hydrogels cross-linked with functionalized Fe3 O4 nanoparticles were prepared. Fe3 O4 nanoparticles covalently linked to the polymer chains. These magnetic hydrogels are capable to remove MB and Cd from aqueous solutions. The saturated hydrogels can be regenerated and reused by washing with sea water. Abstract: Magnetic hydrogels based on carboxymethylcellulose (CMC) were prepared using magnetite (Fe3 O4 ) nanoparticles (NPs) functionalized with 3-aminopropyltrimethoxysilane (APTMS) as cross-linker. In this hybrid organic-inorganic hydrogel, magnetite NPs are covalently bonded to the polymer chains. The CMC-Fe3 O4 hydrogel was characterized by means of Attenuated Total Reflection Fourier Transform Infra Red Spectroscopy (ATR-FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The equilibrium swelling degree of the CMC-Fe3 O4 hydrogels was measured in deionized water as well as in artificial and natural sea water. Bioassays were performed in order to assess the ecosafety of these magnetic hydrogels by testing any potential effect on the growth rate of marine microalgae Dunaliella tertiolecta . The capability of the CMC-Fe3 O4 hydrogel to adsorb organic and inorganic pollutants was tested on solutions of methylene blue (MB) and CdCl2 in deionized and sea water as model systems. The CMC-Fe3 O4 hydrogel is capable to adsorb both MB and Cd(II) in deionized water. On the other hand, the adsorption capacity is strongly reduced in sea water, due to the ions in solution which decrease the electrostatic attraction between the carboxylate groups of CMC and the positive charge of MB and Cd(II).